Ablation-resistant long fiber reinforced nylon material for battery pack

By adding long fiber reinforced materials, flame retardants and other modifiers to the nylon materials used in the battery pack, the problems of insufficient flame retardant performance, poor processing performance and poor ablation resistance of traditional nylon materials are solved, and higher flame retardant performance, mechanical performance and ablation resistance are achieved to ensure the safety and reliability of the battery pack.

CN119529519APending Publication Date: 2025-02-28HANGZHOU ZETONG NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411819920.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The nylon materials used in traditional battery packs have insufficient flame retardant performance, poor processing performance, and poor ablation resistance, which leads to prone to ablation in high temperatures or fires, losing mechanical strength and structural integrity, and thus causing more serious fires or explosions.

Method used

A battery-packed ablation-resistant long fiber reinforced nylon material is used, and its raw material components include nylon resin powder, long fiber reinforced material, diethyl aluminum hypophosphate masterbatch, bromo-antimony composite masterbatch, montmorillonite, aluminum hydroxide, nanosilica, nanocarbon tubes, antioxidants, lubricants, compatibility agents, nucleating agents and anti-ultraviolet agents. Through specific mixing and preparation methods, these components are ensured to be evenly distributed in nylon materials, thereby improving the flame retardant, mechanical and ablation resistance of the material.

Benefits of technology

It significantly improves the flame retardant properties, mechanical properties and ablation resistance of nylon materials, and can more effectively prevent ablation and fire spread in high temperatures or fire situations, ensuring the safety and reliability of the battery pack.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005182859230000181
    Figure BDA0005182859230000181
Patent Text Reader

Abstract

The invention discloses an ablation-resistant long-fiber reinforced nylon material for a battery pack, and relates to the technical field of nylon materials, the ablation-resistant long-fiber reinforced nylon material comprises the following raw material components by weight: 60-80 parts of nylon resin powder, 30-50 parts of a long-fiber reinforced material, 10-18 parts of aluminum diethylhypophosphite master batch, 8-15 parts of bromine-antimony composite master batch, 3-7 parts of montmorillonite, 12-20 parts of aluminum hydroxide, and 2-6 parts of nano-silica. The composite material is prepared from the following components in parts by weight: 1-4 parts of carbon nanotubes, 0.5-1.2 parts of an antioxidant I, 0.3-0.8 part of a lubricant I, 2-5 parts of a compatilizer, 0.1-0.4 part of a nucleating agent and 0.2-0.6 part of an anti-ultraviolet agent. By adding the diethyl aluminum hypophosphite master batch, the flame retardant property of the nylon material is improved, the processability of the nylon material is improved, the ablation resistance of the nylon material is improved, and the problems of insufficient flame retardant property, poor processability and poor ablation resistance of the nylon material can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nylon materials, and in particular to an ablation-resistant long-fiber reinforced nylon material for a battery pack. Background Art

[0002] Traditional nylon materials used in battery packs have insufficient flame retardancy, poor processing performance, and poor ablation resistance. Under high temperature or fire conditions, traditional nylon materials ablate quickly and lose their original mechanical strength and structural integrity, which in turn causes the battery pack shell to rupture, exposing the internal battery cells and causing more serious fires or explosions. The nylon material used in the battery pack of the present application can solve the problems of insufficient flame retardancy, poor processing performance, and poor ablation resistance of nylon materials.

[0003] The defects of existing nylon materials are:

[0004] 1. Patent document CN117844235B discloses a highly wear-resistant nylon material. The document mainly considers how to improve the wear resistance of nylon materials, but does not consider how to solve the problems of insufficient flame retardancy, poor processing performance and poor ablation resistance of nylon materials;

[0005] 2. Patent document CN109943068B discloses a high temperature resistant nylon material and an electroplated nylon material and a preparation method and application thereof. The document mainly considers how to overcome the problem that the existing nylon material has a low thermal deformation temperature and is difficult to electroplate at a high temperature of 170-190°C, but does not consider how to solve the problems of insufficient flame retardancy, poor anti-drip performance, poor processing performance and poor mechanical strength of nylon materials;

[0006] 3. Patent document CN107523048B discloses a wear-resistant nylon material and a preparation method thereof. The document mainly considers how to improve the friction coefficient and high toughness, but does not consider how to improve the high temperature resistance and fire resistance, mechanical strength and processing performance of the nylon material;

[0007] 4. Patent document CN108892947B discloses a halogen-free flame-retardant thermally conductive nylon material. This document mainly considers how to improve the thermal conductivity and flame retardant effect of nylon materials, but does not consider how to improve the quality and reliability of nylon materials and verify the mechanical properties and flame retardant properties of ablation-resistant long fiber reinforced nylon materials for battery packs. Summary of the invention

[0008] The object of the present invention is to provide an ablation-resistant long fiber reinforced nylon material for a battery pack to solve the problems raised in the above-mentioned background technology.

[0009] To achieve the above object, the present invention provides the following technical solution: an ablation-resistant long fiber reinforced nylon material for a battery pack, wherein the weight parts of the raw material components include: 60-80 parts of nylon resin powder, 30-50 parts of long fiber reinforced material, 10-18 parts of diethyl aluminum hypophosphite masterbatch, 8-15 parts of bromine-antimony composite masterbatch, 3-7 parts of montmorillonite, 12-20 parts of aluminum hydroxide, 2-6 parts of nano silicon dioxide, 1-4 parts of nano carbon tubes, 0.5-1.2 parts of antioxidant, 0.3-0.8 parts of lubricant, 2-5 parts of compatibilizer, 0.1-0.4 parts of nucleating agent, and 0.2-0.6 parts of anti-ultraviolet agent;

[0010] The preparation method of nylon material includes:

[0011] Step S1, preparing diethyl aluminum hypophosphite masterbatch;

[0012] Step S2, preparing bromine-antimony composite masterbatch:

[0013] Step S3, putting 72 parts of nylon resin powder, 34 parts of long fiber reinforcement material, 17 parts of diethyl aluminum hypophosphite masterbatch, 11 parts of bromine-antimony composite masterbatch, 6 parts of montmorillonite, 16 parts of aluminum hydroxide, 4 parts of nano silicon dioxide, 1.2 parts of nano carbon tubes, 0.8 parts of antioxidant 1, 0.6 parts of lubricant 1, 3.1 parts of compatibilizer, 0.3 parts of nucleating agent and 0.4 parts of anti-ultraviolet agent into a high-speed mixer and mixing evenly;

[0014] Step S4, passing the mixed raw materials through a twin-screw extruder into an immersion tank;

[0015] Step S5, performing strip drawing, cooling, pelletizing and drying processes;

[0016] Step S6, performing secondary pelletizing and drying;

[0017] Step S7: post-processing the pelletized nylon material particles and performing performance testing.

[0018] Preferably, the long fiber reinforcement material includes glass fiber, carbon fiber and aramid fiber, and the proportions of glass fiber, carbon fiber and aramid fiber are 42.3%, 27.6% and 29.1% respectively;

[0019] The forms of glass fiber, carbon fiber and aramid fiber are chopped fiber, continuous fiber bundle and chopped fiber, respectively.

[0020] Preferably, the antioxidant 1, lubricant 1, compatibilizer, nucleating agent and UV inhibitor are disulfide, polyether modified silicone oil, maleic anhydride grafted ethylene-ethyl acrylate copolymer, 2,2'-methylenebis(4,6-di-tert-butylphenyl) sodium phosphate and 2-(2-hydroxy-5-methylphenyl)benzotriazole respectively.

[0021] Preferably, the dispersant 1, the antioxidant 2 and the lubricant 2 are ethylene bisstearamide, antioxidant 1098 and calcium stearate respectively;

[0022] The brominated flame retardant is octabromoether, and the antimony flame retardant is antimony trioxide;

[0023] The anti-dripping agent, the adhesive, the second dispersant and the filler are polyvinylidene fluoride, polyolefin wax adhesive, stearic acid monoglyceride and mica powder respectively.

[0024] Preferably, step S1 further includes:

[0025] Step S11: adding 573-600 parts by weight of carrier resin into a high-speed mixer, adding 380-400 parts by weight of diethyl aluminum hypophosphite powder, 12-15 parts by weight of dispersant 1, 3-5 parts by weight of antioxidant 2 and 5-7 parts by weight of lubricant 2, stirring in the high-speed mixer for 25 minutes at a stirring speed of about 700 rpm to fully mix the components;

[0026] Step S12: Add the premixed materials into the hopper of the twin-screw extruder, set the temperature of the feed section to 190°C, the temperature of the middle section to 230°C, and the temperature of the discharge section to 240°C. The extruded melt is extruded into strips through a die head, and then enters a water cooling tank for cooling and solidification, and is pelletized by a pelletizer to obtain diethyl aluminum hypophosphite masterbatch.

[0027] Preferably, step S2 further includes:

[0028] Step S21: drying the carrier resin at a temperature of 60° C. for 8 hours until the moisture content of the carrier resin is less than 0.05%;

[0029] Step S22: pre-mixing the brominated flame retardant, the antimony flame retardant and the carrier resin in a high-speed mixer in a mass ratio of 6:2:25, adding an anti-dripping agent, an adhesive, a second dispersant and a filler in an amount of 5% of the total material mass, wherein the anti-dripping agent accounts for 1%, the adhesive accounts for 1.5%, the second dispersant accounts for 1%, and the filler accounts for 1.5%. The mixer speed is set at 900 rpm and the mixing time is 20 minutes to preliminarily mix the components evenly.

[0030] Step S23: The premixed materials are then mixed for a second time by mixing at a low speed for a long time, with a rotation speed of 300 rpm and a mixing time of 40 minutes.

[0031] Preferably, step S4 further includes:

[0032] Step S41: the screw length-to-diameter ratio of the twin-screw extruder is 48:1, and the screw speed is set to 380 rpm;

[0033] Step S42: the temperature of the feed section is set to 195°C, the temperature of the middle section is divided into two zones, the temperature of the first middle section is 232°C, the temperature of the second middle section is 238°C, the temperature of the discharge section is 245°C, the temperature of the die head is 240°C, and the vacuum degree is maintained at -0.08MPa during the extrusion process;

[0034] Step S43: the extruded material enters an immersion tank, in which the functional additive solution consists of 5% of a nano titanium dioxide dispersion modified by a silane coupling agent, 3% of an organic phosphate plasticizer and 92% of an ethanol solvent, and the material stays in the immersion tank for 3 minutes.

[0035] Preferably, step S5 further includes:

[0036] Step S51: the impregnated material enters a drawing machine, the screw diameter of the drawing machine is 40 mm, the screw speed is 350 rpm, the die aperture of the drawing machine is 3 mm, and the pulling speed is 4 m / min;

[0037] Step S52: the stretched material enters a cooling water tank for cooling. The water temperature of the cooling water tank is controlled at 18°C. The length of the cooling water tank is 5 meters. After the material is fully cooled to below 40°C, it enters a pelletizer for pelletizing. The tool speed is 600 rpm. The pelletizing size is 3mm×3mm×5mm.

[0038] Step S53: the pelletized material enters a vacuum drying oven for drying at a drying temperature of 70° C., a vacuum degree of -0.06 MPa, and a drying time of 3 hours.

[0039] Preferably, step S6 further includes:

[0040] Step S61: the dried particles are again put into a pelletizer for secondary pelletizing, using a staggered multi-blade cutter with a cutter speed of 550 rpm. The size error of the pelletized particles is ±0.1 mm.

[0041] Step S62: the granules after secondary granulation enter the fluidized bed dryer, the drying gas is nitrogen, the nitrogen flow rate is 10 cubic meters per hour, the drying temperature is 65°C, and the drying time is 2 hours, until the moisture content of the granules is less than 0.03%.

[0042] Preferably, step S7 further includes:

[0043] Step S71: performing a mechanical property test, the mechanical property test including a tensile strength test and a bending strength test;

[0044] When conducting the tensile strength test, prepare the standard specimen according to the national standard GB / T1040.2-2006, install the specimen on the fixture of the universal material testing machine, set the tensile speed to 5 mm / min, start the testing machine, record the load-displacement curve of the specimen during the tensile process until the specimen breaks, calculate the tensile strength based on the maximum load at break and the original cross-sectional area of ​​the specimen, test 5 specimens, and take the average value as the final result;

[0045] When conducting the bending strength test, the standard specimens were prepared according to the national standard GB / T9341-2008, and the specimens were placed on the support device of the three-point bending test machine. The span was set to 64 mm, and the bending load was applied at a speed of 2 mm / min. The load-displacement curve was recorded until the specimen broke. The bending strength was calculated, and 5 specimens were tested, and the average value was taken as the final result.

[0046] Step S72: When conducting a vertical combustion test, make a sample of 125mm×13mm×3mm with nylon material particles, fix it vertically on the fixture of the vertical combustion tester, ignite the flame, adjust the flame height to about 20mm, and the flame temperature to 800-1000℃. Make the flame contact the bottom of the sample for 10s and then move away. Record the flame burning time and the afterflame and afterglow time after combustion, and observe whether there is dripping during the combustion process.

[0047] Compared with the prior art, the present invention has the following beneficial effects:

[0048] 1. The present invention adds diethyl aluminum hypophosphite masterbatch. As an inorganic flame retardant, diethyl aluminum hypophosphite has excellent flame retardant effect. When diethyl aluminum hypophosphite is decomposed by heat, it absorbs a large amount of heat and generates water vapor, thereby effectively slowing down the burning speed of nylon materials. In addition, the aluminum oxide layer generated by the decomposition of diethyl aluminum hypophosphite can also isolate oxygen, further preventing the combustion. By adding diethyl aluminum hypophosphite to the nylon material in the form of masterbatch, the uniform distribution of diethyl aluminum hypophosphite in the nylon matrix can be ensured, thereby improving the flame retardant properties of the entire nylon material. When preparing the diethyl aluminum hypophosphite masterbatch, an appropriate amount of dispersant ethylene bis stearamide, antioxidant 1098 and lubricant calcium stearate are added. These additives help the uniform dispersion of diethyl aluminum hypophosphite in the carrier resin and prevent the agglomeration of diethyl aluminum hypophosphite particles, thereby improving the processing properties of nylon materials. The uniformly dispersed diethyl aluminum hypophosphite particles can reduce the problems of mold blockage or product surface defects caused by the agglomeration of diethyl aluminum hypophosphite during injection molding or extrusion. In addition to flame retardant properties, diethyl aluminum hypophosphite can also improve the ablation resistance of nylon materials to a certain extent. At high temperatures, the aluminum oxide layer produced by the decomposition of diethyl aluminum hypophosphite can protect the nylon material matrix from high temperature erosion, thereby extending the service life of the nylon material. Therefore, it can solve the problems of insufficient flame retardant properties, poor processing properties and poor ablation resistance of nylon materials.

[0049] 2. The present invention can significantly improve the flame retardant properties of nylon materials by adding bromine-antimony composite masterbatch, the synergistic effect of bromine flame retardant octabromoether and antimony flame retardant antimony trioxide. Bromine flame retardant releases bromine free radicals during combustion, captures free radicals in the combustion chain reaction, thereby slowing down or interrupting the combustion process, while antimony flame retardant can promote the formation of carbon layer, isolate oxygen and heat, and further prevent combustion. By adding these two flame retardants to nylon materials in the form of masterbatch, their uniform distribution in the nylon matrix can be ensured, thereby improving the flame retardant level of the entire nylon material and meeting the battery pack's requirements for high flame retardant properties. The addition of anti-dripping agent polyvinylidene fluoride can significantly improve the anti-dripping performance of nylon materials during the combustion process, and can form a protective film on the surface of nylon materials to prevent the formation and dripping of molten droplets, thereby preventing the spread of fire. The addition of adhesive polyolefin wax adhesives can help improve the compatibility between the flame retardant and the nylon matrix, improve the processing performance and mechanical strength of the nylon material, and make the flame retardant particles better dispersed in the nylon matrix, reduce agglomeration, and thus improve the overall performance of the nylon material. The addition of dispersant distearic acid monoglyceride can also help improve the dispersibility of the flame retardant in the nylon matrix, further improve the processing performance and mechanical strength of the nylon material. The addition of filler mica powder can improve the hardness and wear resistance of the nylon material to a certain extent, and also help reduce the cost of nylon materials, thereby solving the problems of insufficient flame retardancy, poor anti-dripping performance, and poor processing performance and mechanical strength of nylon materials.

[0050] 3. The present invention adds long fiber reinforcement materials in different forms, and the long fiber reinforcement materials include glass fiber, carbon fiber and aramid fiber. The proportions of glass fiber, carbon fiber and aramid fiber are 42.3%, 27.6% and 29.1% respectively, and the forms of glass fiber, carbon fiber and aramid fiber are chopped fiber, continuous fiber bundle and chopped fiber respectively. Glass fiber, carbon fiber and aramid fiber all have high thermal stability and flame retardancy, and can effectively improve the high temperature resistance and fire resistance of nylon materials, which is very important for the safety of battery packs, especially in the case of high temperature or fire, it can reduce the risk of thermal runaway. At the same time, glass fiber, carbon fiber and aramid fiber are all high-performance reinforcement materials, which can significantly improve the tensile strength, bending strength and impact toughness of nylon materials, making the outer shell of the battery pack more durable, able to withstand greater external impact and extrusion, and protect the internal battery cells from damage. By selecting fibers of different forms, short-cut fibers are easily dispersed in the resin matrix, while continuous fiber bundles can provide better directional reinforcement effects. This combination helps to optimize the processing performance of nylon materials. In addition, the density of carbon fiber and aramid fiber is lower than that of traditional metal materials. Their addition can effectively reduce the weight of the battery pack while ensuring the strength of the nylon material, which is of great significance for improving the endurance and energy efficiency of electric vehicles. Therefore, it can solve the problem of how to improve the high temperature resistance and fire resistance, mechanical strength and processing performance of nylon materials.

[0051] 4. The present invention conducts mechanical property tests and vertical combustion tests on the prepared ablation-resistant long fiber reinforced nylon material for battery packs, and the mechanical property tests include tensile strength tests and bending strength tests. By conducting strict tests in accordance with national standards GB / T1040.2-2006 and GB / T9341-2008, it can be ensured that the prepared ablation-resistant long fiber reinforced nylon material for battery packs has sufficient tensile strength and bending strength, thereby meeting the requirements of the battery pack for the strength of nylon materials in practical applications. By testing in accordance with the UL94 standard, the flame retardant grade of the nylon material can be accurately evaluated to ensure that the nylon material has a lower flame propagation speed, a shorter burning time and afterflame, afterglow time, and good anti-dripping performance during the combustion process. It is crucial to the safety performance of the battery pack, and can effectively prevent the battery pack from thermal runaway and explosion in extreme situations such as fire. By implementing mechanical property tests and vertical combustion tests, a comprehensive quality assessment of the prepared ablation-resistant long fiber reinforced nylon material for battery packs can be performed. It helps to timely discover possible problems in the preparation process of nylon materials, so as to make timely adjustments and optimizations to improve the quality and reliability of nylon materials. Therefore, it can solve the problem of how to improve the quality and reliability of nylon materials and verify the mechanical properties and flame retardant properties of ablation-resistant long fiber reinforced nylon materials for battery packs. DETAILED DESCRIPTION

[0052] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0053] Embodiment 1:

[0054] An ablation-resistant long fiber reinforced nylon material for a battery pack, the raw material components include, by weight: 60-80 parts of nylon resin powder, 30-50 parts of long fiber reinforcement material, 10-18 parts of diethyl aluminum hypophosphite masterbatch, 8-15 parts of bromine-antimony composite masterbatch, 3-7 parts of montmorillonite, 12-20 parts of aluminum hydroxide, 2-6 parts of nano silicon dioxide, 1-4 parts of nano carbon tubes, 0.5-1.2 parts of antioxidant, 0.3-0.8 parts of lubricant, 2-5 parts of compatibilizer, 0.1-0.4 parts of nucleating agent, 0.2-0.6 parts of anti-ultraviolet agent;

[0055] Long fiber reinforced materials include glass fiber, carbon fiber and aramid fiber, with the proportions of glass fiber, carbon fiber and aramid fiber being 42.3%, 27.6% and 29.1% respectively.

[0056] The forms of glass fiber, carbon fiber and aramid fiber are chopped fiber, continuous fiber bundle and chopped fiber, respectively.

[0057] Furthermore, nylon resin powder as a matrix material provides the main mechanical properties and processing properties, long fiber reinforcement material can significantly improve the strength, rigidity and ablation resistance of nylon materials, diethyl aluminum hypophosphite masterbatch as a flame retardant improves the flame retardant properties of nylon materials, bromine-antimony composite masterbatch cooperates with diethyl aluminum hypophosphite masterbatch to further improve the flame retardant properties of nylon materials.

[0058] Montmorillonite is used as a nanofiller to improve the mechanical properties and thermal stability of the material. Hydroxide is used as a flame retardant filler, synergistically with diethylaluminum hypophosphite masterbatch and bromine-antimony composite masterbatch to improve the flame retardant properties of nylon materials. Nano-silicon dioxide can improve the wear resistance, hardness and thermal stability of nylon materials. Nano-carbon tubes can improve the conductivity, thermal stability and mechanical properties of the material.

[0059] Antioxidants prevent nylon materials from oxidative degradation during processing and use. Lubricants are used to improve the processing performance of nylon materials and reduce mold wear. Compatibilizers can improve the compatibility between the components and ensure the uniformity and stability of nylon materials. Nucleating agents are used to promote the crystallization of materials and improve the mechanical properties and thermal stability of nylon materials. Anti-ultraviolet agents can prevent nylon materials from aging and degradation under ultraviolet rays.

[0060] The glass fiber is in the form of short fibers, providing high strength and rigidity, as well as good ablation resistance. The carbon fiber is in the form of continuous fiber bundles, providing excellent mechanical properties and thermal stability while reducing the weight of nylon materials. The aramid fiber is in the form of short fibers, providing high strength, high modulus and good chemical corrosion resistance.

[0061] Embodiment 2:

[0062] A ablation-resistant long fiber reinforced nylon material for a battery pack, wherein an antioxidant, a lubricant, a compatibilizer, a nucleating agent and an anti-ultraviolet agent are disulfide, polyether-modified silicone oil, maleic anhydride grafted ethylene-ethyl acrylate copolymer, 2,2'-methylenebis(4,6-di-tert-butylphenyl) sodium phosphate and 2-(2-hydroxy-5-methylphenyl)benzotriazole, respectively.

[0063] Furthermore, the antioxidant is disulfide, which belongs to the disulfide antioxidant class, the lubricant is polyether modified silicone oil, which belongs to the polyether modified silicone oil lubricant, the compatibilizer is maleic anhydride grafted ethylene-ethyl acrylate copolymer, which belongs to the maleic anhydride grafted copolymer compatibilizer, the nucleating agent is 2,2'-methylenebis(4,6-di-tert-butylphenyl) sodium phosphate, which belongs to the organic phosphate nucleating agent, and the UV inhibitor is 2-(2-hydroxy-5-methylphenyl)benzotriazole, which belongs to the benzotriazole UV inhibitor.

[0064] Embodiment three:

[0065] An ablation-resistant long fiber reinforced nylon material for a battery pack, wherein the preparation method of the nylon material comprises:

[0066] Step S1, preparing diethyl aluminum hypophosphite masterbatch;

[0067] Step S1 also includes:

[0068] Step S11: adding 573-600 parts by weight of carrier resin into a high-speed mixer, adding 380-400 parts by weight of diethyl aluminum hypophosphite powder, 12-15 parts by weight of dispersant 1, 3-5 parts by weight of antioxidant 2 and 5-7 parts by weight of lubricant 2, stirring in the high-speed mixer for 25 minutes at a stirring speed of about 700 rpm to fully mix the components;

[0069] Step S12: Add the premixed materials into the hopper of the twin-screw extruder, set the temperature of the feed section to 190°C, the temperature of the middle section to 230°C, and the temperature of the discharge section to 240°C. The extruded melt is extruded into strips through a die head, and then enters a water cooling tank for cooling and solidification, and is pelletized by a pelletizer to obtain diethyl aluminum hypophosphite masterbatch.

[0070] The dispersant 1, antioxidant 2 and lubricant 2 are ethylene bisstearamide, antioxidant 1098 and calcium stearate respectively.

[0071] Furthermore, the carrier resin serves as the basis of the masterbatch, the diethyl aluminum phosphite powder serves as a flame retardant, the dispersant monoethylene bisstearamide helps to evenly disperse the diethyl aluminum phosphite powder in the carrier resin, the antioxidant 1098 prevents the nylon material from being degraded due to oxidation during processing and use, and the lubricant calcium distearate improves the processing fluidity of the nylon material and reduces friction and wear.

[0072] Embodiment 4:

[0073] An ablation-resistant long fiber reinforced nylon material for a battery pack, wherein the preparation method of the nylon material comprises:

[0074] Step S2, preparing bromine-antimony composite masterbatch:

[0075] Step S2 also includes:

[0076] Step S21: drying the carrier resin at a temperature of 60° C. for 8 hours until the moisture content of the carrier resin is less than 0.05%;

[0077] Step S22: pre-mixing the brominated flame retardant, the antimony flame retardant and the carrier resin in a high-speed mixer in a mass ratio of 6:2:25, adding an anti-dripping agent, an adhesive, a second dispersant and a filler in an amount of 5% of the total material mass, wherein the anti-dripping agent accounts for 1%, the adhesive accounts for 1.5%, the second dispersant accounts for 1%, and the filler accounts for 1.5%. The mixer speed is set at 900 rpm and the mixing time is 20 minutes to preliminarily mix the components evenly.

[0078] Step S23: The premixed materials are then mixed for a second time, using a low-speed, long-term mixing method with a rotation speed of 300 rpm and a mixing time of 40 minutes.

[0079] The brominated flame retardant is octabromoether, and the antimony flame retardant is antimony trioxide;

[0080] The anti-dripping agent, the adhesive, the second dispersant and the filler are polyvinylidene fluoride, polyolefin wax adhesive, stearic acid monoglyceride and mica powder respectively.

[0081] Furthermore, the carrier resin is dried at a drying temperature of 60°C for 8 hours until the moisture content of the carrier resin is less than 0.05%, thereby effectively removing moisture from the carrier resin and preventing the resin from being degraded due to excessive temperature. The moisture content in the carrier resin is ensured to be less than 0.05%, thereby ensuring the stability of subsequent processing and product quality.

[0082] Octabromoether, as a commonly used brominated flame retardant, has excellent flame retardant properties and thermal stability, and is suitable for use in high-temperature environments of battery packs. Antimony trioxide, as an antimony flame retardant, works synergistically with brominated flame retardants to significantly improve the flame retardant properties of nylon materials.

[0083] The anti-dripping agent polyvinylidene fluoride forms a protective layer during the combustion process to prevent the generation of molten droplets, thereby improving the flame retardant properties of the material. The adhesive polyolefin wax adhesive is used to improve the adhesion between the components and ensure the integrity and stability of the masterbatch. The dispersant distearic acid monoglyceride helps to evenly disperse the brominated flame retardant and antimony flame retardant in the carrier resin, improving the processing performance and flame retardant properties of the masterbatch. The filler mica powder is used to improve the mechanical properties and thermal stability of the material while reducing costs.

[0084] Embodiment five:

[0085] An ablation-resistant long fiber reinforced nylon material for a battery pack, wherein the preparation method of the nylon material comprises:

[0086] Step S3, putting 78 parts of nylon resin powder, 37 parts of long fiber reinforcement material, 17 parts of diethyl aluminum hypophosphite masterbatch, 11 parts of bromine-antimony composite masterbatch, 6 parts of montmorillonite, 16 parts of aluminum hydroxide, 4 parts of nano silicon dioxide, 1.2 parts of nano carbon tubes, 0.8 parts of antioxidant 1, 0.6 parts of lubricant 1, 3.1 parts of compatibilizer, 0.3 parts of nucleating agent and 0.4 parts of anti-ultraviolet agent into a high-speed mixer and mixing evenly;

[0087] Embodiment six:

[0088] An ablation-resistant long fiber reinforced nylon material for a battery pack, wherein the preparation method of the nylon material comprises:

[0089] Step S3, putting 78 parts of nylon resin powder, 37 parts of long fiber reinforcement material, 17 parts of diethyl aluminum hypophosphite masterbatch, 6 parts of montmorillonite, 16 parts of aluminum hydroxide, 4 parts of nano silicon dioxide, 1.2 parts of nano carbon tubes, 0.8 parts of antioxidant 1, 0.6 parts of lubricant 1, 3.1 parts of compatibilizer, 0.3 parts of nucleating agent and 0.4 parts of anti-ultraviolet agent into a high-speed mixer and mixing evenly;

[0090] Embodiment seven:

[0091] An ablation-resistant long fiber reinforced nylon material for a battery pack, wherein the preparation method of the nylon material comprises:

[0092] Step S3, putting 72 parts of nylon resin powder, 34 parts of long fiber reinforcement material, 11 parts of bromine-antimony composite masterbatch, 6 parts of montmorillonite, 16 parts of aluminum hydroxide, 4 parts of nano-silicon dioxide, 1.2 parts of nano-carbon tubes, 0.8 parts of antioxidant 1, 0.6 parts of lubricant 1, 3.1 parts of compatibilizer, 0.3 parts of nucleating agent and 0.4 parts of anti-ultraviolet agent into a high-speed mixer and mixing evenly;

[0093] Embodiment eight:

[0094] An ablation-resistant long fiber reinforced nylon material for a battery pack, wherein the preparation method of the nylon material comprises:

[0095] Step S3, putting 72 parts of nylon resin powder, 34 parts of long fiber reinforcement material, 6 parts of montmorillonite, 16 parts of aluminum hydroxide, 4 parts of nano-silicon dioxide, 1.2 parts of nano-carbon tubes, 0.8 parts of antioxidant 1, 0.6 parts of lubricant 1, 3.1 parts of compatibilizer, 0.3 parts of nucleating agent and 0.4 parts of anti-ultraviolet agent into a high-speed mixer and mixing evenly;

[0096] Embodiment nine:

[0097] An ablation-resistant long fiber reinforced nylon material for a battery pack, wherein the preparation method of the nylon material comprises:

[0098] Step S4, passing the mixed raw materials through a twin-screw extruder into an immersion tank;

[0099] Step S4 also includes:

[0100] Step S41: the screw length-to-diameter ratio of the twin-screw extruder is 48:1, and the screw speed is set to 380 rpm;

[0101] Step S42: the temperature of the feed section is set to 195°C, the temperature of the middle section is divided into two zones, the temperature of the first middle section is 232°C, the temperature of the second middle section is 238°C, the temperature of the discharge section is 245°C, the temperature of the die head is 240°C, and the vacuum degree is maintained at -0.08MPa during the extrusion process;

[0102] Step S43: the extruded material enters an immersion tank, in which the functional additive solution consists of 5% of a nano titanium dioxide dispersion modified by a silane coupling agent, 3% of an organic phosphate plasticizer and 92% of an ethanol solvent, and the material stays in the immersion tank for 3 minutes.

[0103] Furthermore, the screw aspect ratio of the twin-screw extruder is set to 48:1, and the screw speed is adjusted to 380 rpm, which is conducive to the full mixing and plasticization of the raw materials in the extruder. The feed section is the area where the material just enters the twin-screw extruder. The temperature is set to 195°C to allow the material to begin to gradually soften and melt after entering the extruder, which is convenient for further mixing and advancement under the action of the screw.

[0104] The temperature of the first intermediate section is set to 232°C. At this temperature, the mixing and plasticization of the materials will be further deepened, and the interaction between the raw material components will be more sufficient. As the materials advance in the extruder, setting a slightly higher temperature of 238°C will help to further improve the plasticization effect of the materials, making the materials more uniform and delicate, and ensuring that the final extruded materials have good rheological properties and molding properties. The discharge section is the area where the materials are about to leave the extruder. The temperature is set to 245°C to allow the materials to maintain good fluidity and plasticity when leaving the extruder, so that they can be smoothly extruded through the die head into the desired shape such as strips, and can also maintain a good state when entering the subsequent operations such as the dipping tank.

[0105] The die head is the final part where the material is extruded and formed. The temperature is set to 240°C, which can make the surface of the extruded material smooth and stable in size when passing through the die head, avoiding problems such as surface defects or irregular shapes. By maintaining a vacuum degree of -0.08MPa, air, moisture and some volatile small molecules that may be produced in the material are removed during the extrusion process to avoid these substances remaining in the nylon material, causing bubbles and internal defects in the nylon material, affecting the performance of the nylon material, and can effectively improve the density and quality of the nylon material.

[0106] Silane coupling agent can improve the interfacial compatibility between nano titanium dioxide and nylon matrix and other raw material components. Nano titanium dioxide can improve the heat resistance and corrosion resistance of nylon materials. After being modified by silane coupling agent, it can be better dispersed in the system. Plasticizer can increase the flexibility and plasticity of nylon materials. Organic phosphate plasticizer can be inserted between nylon molecular chains to reduce the interaction force between molecular chains, making nylon materials easier to deform during processing. At the same time, it can also maintain a certain flexibility during use. For nylon materials for battery packs, it helps to better adapt to the shape change requirements of battery packs under different working conditions. Ethanol is used as a solvent to evenly disperse the nano titanium dioxide dispersion modified by silane coupling agent and organic phosphate plasticizer in the solution to form a stable immersion tank functional additive solution so that the materials can fully contact and absorb these functional additives in the immersion tank.

[0107] Embodiment ten:

[0108] An ablation-resistant long fiber reinforced nylon material for a battery pack, wherein the preparation method of the nylon material comprises:

[0109] Step S5, performing strip drawing, cooling, pelletizing and drying processes;

[0110] Step S5 also includes:

[0111] Step S51: the impregnated material enters a drawing machine, the screw diameter of the drawing machine is 40 mm, the screw speed is 350 rpm, the die aperture of the drawing machine is 3 mm, and the pulling speed is 4 m / min;

[0112] Step S52: the stretched material enters a cooling water tank for cooling. The water temperature of the cooling water tank is controlled at 18°C. The length of the cooling water tank is 5 meters. After the material is fully cooled to below 40°C, it enters a pelletizer for pelletizing. The tool speed is 600 rpm. The pelletizing size is 3mm×3mm×5mm.

[0113] Step S53: the pelletized material enters a vacuum drying oven for drying at a drying temperature of 70° C., a vacuum degree of -0.06 MPa, and a drying time of 3 hours.

[0114] Furthermore, in the strip drawing process, the diameter of the rod drawing machine screw is 40mm, ensuring stable material transportation and uniform plasticization. The screw speed of 350 rpm allows the material to be properly advanced and further mixed, reducing the risk of degradation and ensuring continuous and stable strip drawing. The 3mm die head aperture determines the thickness of the strip, which is conducive to subsequent cooling and pelletizing. If the aperture is too small, the resistance is large, and if it is too large, it is not conducive to subsequent processing and performance control. The 4m / min traction speed is combined with the screw speed to stretch the material into a strip with both strength and uniformity.

[0115] The water temperature of the cooling water tank is 18°C, which can quickly cool down and fix the material's shape and performance. Although low water temperature has fast heat transfer, it is easy to cause stress. High water temperature will slow down cooling and easily cause deformation and adhesion. The 5-meter-long water tank ensures that the material has sufficient time to exchange heat and cool to below 40°C, ensuring uniform cooling to avoid adhesion, deformation and pelletizing problems. After cooling, the tool speed of 600 rpm pelletizes materials below 40°C, taking into account efficiency and precision, avoiding overheating and affecting quality. The pelletizing size is 3mm×3mm×5mm, which meets the fluidity, filling and formability requirements of battery pack manufacturing.

[0116] Finally, it enters the vacuum drying oven. The 70°C drying temperature comprehensively considers heat resistance, water evaporation and energy consumption, which can not only remove water but also prevent thermal degradation. The -0.06MPa vacuum degree reduces the boiling point of water, accelerates vaporization, shortens the drying time, and isolates oxygen to prevent oxidation. The 3-hour drying time is determined based on the initial water content, temperature and vacuum degree, which can make the water content meet the standard and ensure the stability and reliability of nylon material storage and battery pack application.

[0117] Embodiment eleven:

[0118] An ablation-resistant long fiber reinforced nylon material for a battery pack, wherein the preparation method of the nylon material comprises:

[0119] Step S6, performing secondary pelletizing and drying;

[0120] Step S6 also includes:

[0121] Step S61: the dried particles are again put into a pelletizer for secondary pelletizing, using a staggered multi-blade cutter with a cutter speed of 550 rpm. The size error of the pelletized particles is ±0.1 mm.

[0122] Step S62: the granules after secondary granulation enter the fluidized bed dryer, the drying gas is nitrogen, the nitrogen flow rate is 10 cubic meters per hour, the drying temperature is 65°C, and the drying time is 2 hours, until the moisture content of the granules is less than 0.03%.

[0123] Furthermore, a staggered multi-blade tool is used for secondary pelletizing. The staggered multi-blade tool cuts in multiple directions during cutting, making the cutting surface of the particles smooth and flat, reducing stress concentration, reducing the risk of crack damage, improving pelletizing efficiency and accuracy, and making the particles regular in shape.

[0124] The tool speed is set at 550 rpm to ensure efficient pelletizing, quickly obtain the required size particles, and avoid the softening and deformation of the nylon material due to excessive heat generated by too fast a speed, thereby accurately controlling the size error after pelletizing within the range of ±0.1mm. This high precision is of great significance to battery pack manufacturing, which can enhance the filling and uniformity of nylon materials during subsequent processing and ensure the quality and stable performance of battery pack components.

[0125] Nitrogen is an inert gas that does not react with nylon materials. It can prevent chemical reactions such as oxidation from causing material performance degradation. It is also highly pure and has very low moisture content. It can efficiently remove moisture from particles, ensuring reliable and stable drying results. The nitrogen flow rate is 10 cubic meters per hour. This flow rate can create a suitable airflow in the dryer, allowing fluidized particles to fully contact nitrogen, evenly transfer heat to accelerate moisture evaporation, and constantly turn particles to avoid uneven local drying. If the flow rate is too small, drying will take a long time and affect efficiency; if it is too large, it will impact particles and affect their integrity and dimensional accuracy.

[0126] The drying temperature is 65°C. Taking into account the thermal stability and evaporation rate of nylon, nylon has good performance at this temperature, and the water can evaporate quickly to achieve deep drying. Compared with higher temperatures, it can minimize the potential impact on material performance and ensure the quality of the final product. After 2 hours of drying, the moisture content of the particles dropped to less than 0.03%, which greatly improved the stability of the material, avoided problems such as hydrolysis and dimensional changes caused by water during storage and processing, and provided reliable performance support for battery pack applications.

[0127] Embodiment 12:

[0128] An ablation-resistant long fiber reinforced nylon material for a battery pack, wherein the preparation method of the nylon material comprises:

[0129] Step S7: post-processing the pelletized nylon material particles and performing performance testing.

[0130] Step S7 also includes:

[0131] Step S71: performing a mechanical property test, the mechanical property test including a tensile strength test and a bending strength test;

[0132] When conducting the tensile strength test, prepare the standard specimen according to the national standard GB / T1040.2-2006, install the specimen on the fixture of the universal material testing machine, set the tensile speed to 5 mm / min, start the testing machine, record the load-displacement curve of the specimen during the tensile process until the specimen breaks, calculate the tensile strength based on the maximum load at break and the original cross-sectional area of ​​the specimen, test 5 specimens, and take the average value as the final result;

[0133] When conducting the bending strength test, the standard specimens were prepared according to the national standard GB / T9341-2008, and the specimens were placed on the support device of the three-point bending test machine. The span was set to 64 mm, and the bending load was applied at a speed of 2 mm / min. The load-displacement curve was recorded until the specimen broke. The bending strength was calculated, and 5 specimens were tested, and the average value was taken as the final result.

[0134] Step S72: When conducting a vertical combustion test, make a sample of 125mm×13mm×3mm with nylon material particles, fix it vertically on the fixture of the vertical combustion tester, ignite the flame, adjust the flame height to about 20mm, and the flame temperature to 800-1000℃. Make the flame contact the bottom of the sample for 10s and then move away. Record the flame burning time and the afterflame and afterglow time after combustion, and observe whether there is dripping during the combustion process.

[0135] Further, the test results of the tensile strength test of the ablation-resistant long fiber reinforced nylon materials prepared in Example 5, Example 6, Example 7 and Example 8 are as follows:

[0136] Example No. Tensile strength(MPa) Embodiment 5 125.6 Embodiment 6 122.8 Embodiment 7 118.4 Embodiment 8 114.2

[0137] The test results of the bending strength test of the ablation-resistant long fiber reinforced nylon materials prepared in Example 5, Example 6, Example 7 and Example 8 are as follows:

[0138] Example No. Bending strength(MPa) Embodiment 5 168.5 Embodiment 6 164.2 Embodiment 7 156.8 Embodiment 8 152.3

[0139] The results of the tensile strength test and the flexural strength test show that the tensile strength and flexural strength of Examples 5, 6 and 7 are higher than those of Example 8 which does not add diethylaluminum hypophosphite masterbatch and bromine-antimony composite masterbatch due to the addition of one or two of diethylaluminum hypophosphite masterbatch and bromine-antimony composite masterbatch. The addition of diethylaluminum hypophosphite masterbatch and bromine-antimony composite masterbatch not only improves the flame retardant properties of nylon material, but also enhances the mechanical properties of nylon material to a certain extent.

[0140] The test results of the vertical combustion test of the ablation-resistant long fiber reinforced nylon materials prepared in Example 5, Example 6, Example 7 and Example 8 are as follows:

[0141]

[0142]

[0143] The results of the vertical burning test show that the ablation-resistant long fiber reinforced nylon material prepared in Example 5 performed well in the flame burning test, with a flame burning time of only 5 seconds, and a short afterflame and afterglow time of 2 seconds, and no dripping phenomenon occurred, indicating that the nylon material prepared by adding diethyl aluminum hypophosphite masterbatch and bromine-antimony composite masterbatch has good flame retardant properties and anti-dripping properties, and can effectively suppress the spread of flame in a short time.

[0144] The nylon material of Example 6 also exhibits good flame retardant properties, with a flame burning time of 6 seconds, an afterflame and afterglow time of 3 seconds, and no dripping. Compared with Example 5, its burning time is slightly longer, but the overall flame retardant effect is still significant.

[0145] In the flame combustion test, the flame burning time, afterflame and afterglow time of the nylon material of Example 7 were 8 seconds and 4 seconds respectively. Although there was no dripping phenomenon, its flame retardant performance was reduced compared with that of Examples 5 and 6.

[0146] The nylon material of Example 8 performed relatively poorly in the test, with a flame burning time of 10 seconds, an afterflame and afterglow time of 5 seconds, and dripping. This indicates that the nylon material prepared without adding diethyl aluminum hypophosphite masterbatch and bromine-antimony composite masterbatch is more likely to melt and drip at high temperatures, thereby increasing the risk of fire.

[0147] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. An ablation-resistant long fiber reinforced nylon material for a battery pack, characterized in that: The raw material components include by weight: 60-80 parts of nylon resin powder, 30-50 parts of long fiber reinforcement material, 10-18 parts of diethyl aluminum hypophosphite masterbatch, 8-15 parts of bromine-antimony composite masterbatch, 3-7 parts of montmorillonite, 12-20 parts of aluminum hydroxide, 2-6 parts of nano silicon dioxide, 1-4 parts of nano carbon tubes, 0.5-1.2 parts of antioxidant, 0.3-0.8 parts of lubricant, 2-5 parts of compatibilizer, 0.1-0.4 parts of nucleating agent, and 0.2-0.6 parts of anti-ultraviolet agent; The preparation method of nylon material includes: Step S1, preparing diethyl aluminum hypophosphite masterbatch; Step S2, preparing bromine-antimony composite masterbatch: Step S3, putting 72 parts of nylon resin powder, 34 parts of long fiber reinforcement material, 17 parts of diethyl aluminum hypophosphite masterbatch, 11 parts of bromine-antimony composite masterbatch, 6 parts of montmorillonite, 16 parts of aluminum hydroxide, 4 parts of nano silicon dioxide, 1.2 parts of nano carbon tubes, 0.8 parts of antioxidant 1, 0.6 parts of lubricant 1, 3.1 parts of compatibilizer, 0.3 parts of nucleating agent and 0.4 parts of anti-ultraviolet agent into a high-speed mixer and mixing evenly; Step S4, passing the mixed raw materials through a twin-screw extruder into an immersion tank; Step S5, performing strip drawing, cooling, pelletizing and drying processes; Step S6, performing secondary pelletizing and drying; Step S7: post-processing the pelletized nylon material particles and performing performance testing.

2. The ablation-resistant long fiber reinforced nylon material for a battery pack according to claim 1, characterized in that: Long fiber reinforcement materials include glass fiber, carbon fiber and aramid fiber, with the proportions of glass fiber, carbon fiber and aramid fiber being 42.3%, 27.6% and 29.1% respectively; The forms of glass fiber, carbon fiber and aramid fiber are chopped fiber, continuous fiber bundle and chopped fiber, respectively.

3. The ablation-resistant long fiber reinforced nylon material for a battery pack according to claim 1, characterized in that: The antioxidant 1, lubricant 1, compatibilizer, nucleating agent and anti-ultraviolet agent are disulfide, polyether modified silicone oil, maleic anhydride grafted ethylene-ethyl acrylate copolymer, 2,2'-methylenebis(4,6-di-tert-butylphenyl) sodium phosphate and 2-(2-hydroxy-5-methylphenyl)benzotriazole respectively.

4. The ablation-resistant long fiber reinforced nylon material for a battery pack according to claim 1, characterized in that: Dispersant 1, antioxidant 2 and lubricant 2 are ethylene bis stearamide, antioxidant 1098 and calcium stearate respectively; The brominated flame retardant is octabromoether, and the antimony flame retardant is antimony trioxide; The anti-dripping agent, the adhesive, the second dispersant and the filler are polyvinylidene fluoride, polyolefin wax adhesive, stearic acid monoglyceride and mica powder respectively.

5. The ablation-resistant long fiber reinforced nylon material for a battery pack according to claim 1, characterized in that: Step S1 also includes: Step S11: adding 573-600 parts by weight of carrier resin into a high-speed mixer, adding 380-400 parts by weight of diethyl aluminum hypophosphite powder, 12-15 parts by weight of dispersant 1, 3-5 parts by weight of antioxidant 2 and 5-7 parts by weight of lubricant 2, stirring in the high-speed mixer for 25 minutes at a stirring speed of about 700 rpm to fully mix the components; Step S12: Add the premixed materials into the hopper of the twin-screw extruder, set the temperature of the feed section to 190°C, the temperature of the middle section to 230°C, and the temperature of the discharge section to 240°C. The extruded melt is extruded into strips through a die head, and then enters a water cooling tank for cooling and solidification, and is pelletized by a pelletizer to obtain diethyl aluminum hypophosphite masterbatch.

6. The ablation-resistant long fiber reinforced nylon material for a battery pack according to claim 1, characterized in that: Step S2 also includes: Step S21: drying the carrier resin at a temperature of 60° C. for 8 hours until the moisture content of the carrier resin is less than 0.05%; Step S22: pre-mixing the brominated flame retardant, the antimony flame retardant and the carrier resin in a high-speed mixer in a mass ratio of 6:2:25, adding an anti-dripping agent, an adhesive, a second dispersant and a filler in an amount of 5% of the total material mass, wherein the anti-dripping agent accounts for 1%, the adhesive accounts for 1.5%, the second dispersant accounts for 1%, and the filler accounts for 1.5%. The mixer speed is set at 900 rpm and the mixing time is 20 minutes to preliminarily mix the components evenly. Step S23: The premixed materials are then mixed for a second time, using a low-speed, long-term mixing method with a rotation speed of 300 rpm and a mixing time of 40 minutes.

7. The ablation-resistant long fiber reinforced nylon material for a battery pack according to claim 1, characterized in that: Step S4 also includes: Step S41: the screw length-to-diameter ratio of the twin-screw extruder is 48:1, and the screw speed is set to 380 rpm; Step S42: the temperature of the feed section is set to 195°C, the temperature of the middle section is divided into two zones, the temperature of the first middle section is 232°C, the temperature of the second middle section is 238°C, the temperature of the discharge section is 245°C, the temperature of the die head is 240°C, and the vacuum degree is maintained at -0.08MPa during the extrusion process; Step S43: the extruded material enters an immersion tank, in which the functional additive solution consists of 5% of a nano titanium dioxide dispersion modified by a silane coupling agent, 3% of an organic phosphate plasticizer and 92% of an ethanol solvent, and the material stays in the immersion tank for 3 minutes.

8. The ablation-resistant long fiber reinforced nylon material for a battery pack according to claim 1, characterized in that: Step S5 also includes: Step S51: the impregnated material enters a drawing machine, the screw diameter of the drawing machine is 40 mm, the screw speed is 350 rpm, the die aperture of the drawing machine is 3 mm, and the pulling speed is 4 m / min; Step S52: the stretched material enters a cooling water tank for cooling. The water temperature of the cooling water tank is controlled at 18°C. The length of the cooling water tank is 5 meters. After the material is fully cooled to below 40°C, it enters a pelletizer for pelletizing. The tool speed is 600 rpm. The pelletizing size is 3mm×3mm×5mm. Step S53: the pelletized material enters a vacuum drying oven for drying at a drying temperature of 70° C., a vacuum degree of -0.06 MPa, and a drying time of 3 hours.

9. The ablation-resistant long fiber reinforced nylon material for a battery pack according to claim 1, characterized in that: Step S6 also includes: Step S61: the dried particles are again put into a pelletizer for secondary pelletizing, using a staggered multi-blade cutter with a cutter speed of 550 rpm. The size error of the pelletized particles is ±0.1 mm. Step S62: the granules after secondary granulation enter the fluidized bed dryer, the drying gas is nitrogen, the nitrogen flow rate is 10 cubic meters per hour, the drying temperature is 65°C, and the drying time is 2 hours, until the moisture content of the granules is less than 0.03%.

10. The ablation-resistant long fiber reinforced nylon material for a battery pack according to claim 1, characterized in that: Step S7 also includes: Step S71: performing a mechanical property test, the mechanical property test including a tensile strength test and a bending strength test; When conducting the tensile strength test, prepare the standard specimen according to the national standard GB / T1040.2-2006, install the specimen on the fixture of the universal material testing machine, set the tensile speed to 5 mm / min, start the testing machine, record the load-displacement curve of the specimen during the tensile process until the specimen breaks, calculate the tensile strength based on the maximum load at break and the original cross-sectional area of ​​the specimen, test 5 specimens, and take the average value as the final result; When conducting the bending strength test, the standard specimens were prepared according to the national standard GB / T9341-2008, and the specimens were placed on the support device of the three-point bending test machine. The span was set to 64 mm, and the bending load was applied at a speed of 2 mm / min. The load-displacement curve was recorded until the specimen broke. The bending strength was calculated, and 5 specimens were tested, and the average value was taken as the final result. Step S72: When conducting a vertical combustion test, make a sample of 125mm×13mm×3mm with nylon material particles, fix it vertically on the fixture of the vertical combustion tester, ignite the flame, adjust the flame height to about 20mm, and the flame temperature to 800-1000℃. Make the flame contact the bottom of the sample for 10s and then move away. Record the flame burning time and the afterflame and afterglow time after combustion, and observe whether there is dripping during the combustion process.

Citation Information

Patent Citations

  • Abrasion-resistant nylon materials and their preparation methods

    CN107523048B

  • A halogen-free flame-retardant and thermally conductive nylon material

    CN108892947B

  • A high-temperature resistant nylon material and an electroplated nylon material, their preparation methods and applications

    CN109943068B

  • A highly wear-resistant nylon material

    CN117844235B

Cited By

  • A high-performance flame-retardant reinforced PPA composite material and its production method

    CN119735910A

  • PA composite material as well as preparation method and application thereof

    CN120966239A

  • PA composite material, preparation method and application thereof

    CN120966239B